Botulinum toxin type a spread into non-injected antagonistic muscles causes increased extracellular matrix collagen - Akcan, İsmail Orkun. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2019., 2019)
The present study aims at assessing effects of Botulinum toxin type A (BTXA) on the targeted medial and lateral gastrocnemius muscles in terms of muscle forces and connective tissue content. The particular goal is to test if BTX-A spreads from the injected muscles into the antagonistic anterior crural muscles and to test if those non-injected muscles have collagen wise denser extracellular matrix. For this purpose, an experimental animal study was conducted in the rat lower leg by measuring muscle forces and the density of collagen using histology. In order to assess the effects of BTXA two cases were studied: BTX-A group and control group. Active force production, passive resistance, joint range of motion and connective tissue contents of these cases were compared. Muscle length-force relationships showed active force drops (up to 80%) and narrowing of length range of force exertion for target muscles (by 3 mm). However, also the antagonistic muscles showed force drops (around 20%) indicating inter-antagonistic leakage of BTX-A. In addition, the collagen density increased by 50% and 31% for target muscles, 11% for synergistic muscles, and 43% and 28% for antagonistic muscles. A major finding obtained from histological assessments is denser collagen results in a net increase at extracellular matrix of muscles whether they are targeted by BTX-A injection or not. It is evident that this effect arises from the spread of toxin. Such effect has important clinical implications.|Keywords : Botulinum Toxin, Experimental Animal Study, Histology, Collagen, Extracellular Matrix.
Keywords: Botulinum toxin.; Collagen.; Extracellular matrix.